THE ROLE OF THE VILLAGE DELIBERATIVE BODY IN SUPERVISING VILLAGE FINANCIAL MANAGEMENT - Sihombing, Eka N.A.M; Darmawansyah Sihombing, Rizky (NOMOI Law Review, 2025)
The implementation of village governance is not solely the responsibility of the village head; the Village Consultative Body (BPD) plays a crucial role in implementing the village governance system. One of the roles or functions of the BPD is to oversee the performance of the village head, which also includes oversight of village financial management. However, this role, when associated with the high rate of corruption committed by village heads, indicates that the BPD has not been performing its oversight function optimally, resulting in continued misappropriation. This study employed a normative juridical method with a statute approach . The results of the discussion indicate that in terms of village financial management, it is more technically regulated in the provisions of the Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management. Village financial management is carried out based on the principles of openness, accountability, and participation, and is carried out in an orderly and disciplined budget. In addition, in relation to the Village Consultative Body, the BPD can participate in overseeing village financial management, from planning, implementation to accountability reporting. This is a manifestation of the implementation of the principles of openness and participation which are the foundation for village financial management.